1997
DOI: 10.1136/hrt.77.6.502
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensin converting enzyme and angiotensin II type 1 receptor genotypes with left ventricular function and mass in patients with angiographically normal coronary arteries.

Abstract: Objective-To analyse the potential association of the angiotensin converting enzyme (ACE) and angiotensin II type 1 receptor (ATIR) gene polymorphisms on left ventricular function and mass in patients with normal coronary arteries. Design-Consecutive sample. Setting-University hospital. Subjects-141 consecutive white patients referred for coronary angiography and with angiographically normal coronary arteries. Patients with valvar diseases, cardiomyopathies, or a history of myocardial infarction were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 27 publications
2
25
2
1
Order By: Relevance
“…This lack of association found in our study is reinforced by the subgroup analysis of hypertensive patients included in general population studies. In fact, Lindpaintner et al, 4 Hamon et al 5 and Kupari et al 6 did not find any significant difference in LV mass among the three ACE genotypes, when the subset of hypertensives were analysed separately.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This lack of association found in our study is reinforced by the subgroup analysis of hypertensive patients included in general population studies. In fact, Lindpaintner et al, 4 Hamon et al 5 and Kupari et al 6 did not find any significant difference in LV mass among the three ACE genotypes, when the subset of hypertensives were analysed separately.…”
Section: Discussionmentioning
confidence: 93%
“…[7][8][9] Schunkert et al 3 first reported in 1994 a higher prevalence of the DD genotype in subjects with electrocardiographic evidence of LVH. However, three later studies [4][5][6] failed to confirm this association by assessing LVH by echocardiography. One of these studies, carried out by Lindpaintner et al 4 included a total of 2439 subjects from the Framingham population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study indicated that the AT1 receptor polymorphism that may increase receptor number or sensitivity may not cause CVD directly but it can contribute to the process that is started by other factors such as high renin conditions. Although the above findings suggest a positive association between the ATl-receptor CC polymorphism and certain CVD, negative associations have also been reported in coronary atherosclerosis (45) and left ventricular hypertrophy (46). Recently Hilger et al (47) reported that NC 1166 polymorphism of AT1R does not affect high BP, renal hemodynamic and aldosterone response to infused All.…”
Section: Angiotensin II Type I Receptor (Atir)mentioning
confidence: 96%